Analyzing the development of 4th generation mobile network in China: actor network theory perspective. Issue 1 (12th January 2015) - Shim, Yongwoon; Shin, Dong-Hee
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to provide an in-depth analysis of the process of standards setting based on the case of long-term evolution time division duplex (LTE TDD) deployment in China. Design/methodology/approach – Using actor-network theory (ANT) as a theoretical framework, multi-level analyses are presented to explain the process of adoption of LTE TDD at a global level. Findings – Findings identified the complex interaction between the social and technical aspects of fourth-generation (4G) by highlighting the co-evolving nature, diversity and interface that constitute the next-generation network environment. Research limitations/implications – ANT provides a framework of ideas for describing the process of technology adoption and for developing stories that explain it. Originality/value – The findings shed light on a critical insight of the interrelationships between TD-SCDMA and LTE TDD and identify the policy successes and failures of 4G mobile networks.